MiR-29a-5p engages in the mechanism of diabetic retinopathy by specifically targeting SIRT3 - He, Jianhong; Wei, Shuzhen; Ye, Lingzhi; Liao, Rifang; Zeng, Zhuanping (Gene, 2025)
•MiR-29a-5p was markedly elevated in individuals with DR.•High glucose promotes the expression of miR-29a-5p in RGC-5 cells.•Inhibiting miR-29a-5p expression can alleviate oxidative stress, inflammatory response, and apoptosis in RGC-5 cells under high glucose conditions.•SIRT3 is a target gene of miR-29a-5p, inhibiting miR-29a-5p can promote SIRT3 expression, reduce high glucose induced oxidative stress, inflammatory response and delay the development of DR. Whether miR-29a-5p is associated with Diabetic Retinopathy (DR) is still a subject of ongoing discussion. The current research examines the involvement of miR-29a-5p in regulating apoptosis, oxidative stress, and inflammation of retinal ganglion cells (RGCs) generated by High Glucose (HG). Additionally, we are interested in analyzing the contribution of miR-29a-5p in DRdeveloping. We obtained peripheral blood samples from 7 people with DR and 14 individuals without DR. Subsequently, we conducted biochemical indices analyses and qRT-PCR.We randomly divided RGCs into low glucose groups, HG groups, HG + inhibitor negative control groups, and HG + miR-29a-5p inhibitor groups. SIRT3 siRNA was transfected into RGCs through lipofectamine 3000 reagent.Cell vitality was detected by MTT; qRT-PCR was applied to identify miR-29a-5p expression; Detectionof ROS, SOD, and MDAlevels was quantified using the DCFH-DA, WST-1, and colorimetric methods, respectively; IL-6 and TNF-αcontents were analyzed utilizing ELISA; Dual-luciferase gene reporter experiment was used to examine if SIRT3 is the specific target gene of miR-29a-5p; Flow cytometryevaluatedapoptosisin RGCs; The technique of Western blotting identified the presence of caspase-3 proteins. The expression of miR-29a-5p was markedly elevated in individuals with DR, and it had positive correlations with levels of Total Cholesterol (TC) and Fasting Blood Glucose (FBG).High glucose significantly induced RGC apoptosis and upregulated the miR-29a-5p gene. Transfection of miR-29a-5p inhibitor protected RGCs against HG-induced oxidative injury, inflammation, and apoptosis. Furthermore, the dual-luciferase reporter experiment provided confirmation that SIRT3 was a target gene of miR-29a-5p, as it negatively regulated SIRT3 expression. Notably, SIRT3 knockdown abolished the protection of miR-29a-5p inhibition on RGCs. Suppression of the miR-29a-5p gene safeguards RGCs against harm caused by HG via boosting SIRT3 signaling, which might provide a new prevention and treatment strategy for DR.